Failure and damage analysis of advanced materials - Altenbach, Holm 1956-; Sadowski, Tomasz 1954- (Springer Vienna, 2015)
The papers in this volume present basic concepts and new developments in failure and damage analysis with a focus on advanced materials such as composites, laminates, sandwiches and foams, and also new metallic materials. Starting from some mathematical foundations (limit surfaces, symmetry considerations, invariants) new experimental results and their analysis are shown. Finally, new concepts for failure prediction and analysis will be introduced and discussed as well as new methods of failure and damage prediction for advanced metallic and non-metallic materials. Based on experimental results the traditional methods will be revised.